Evaluation of Cambridge Math Series for grades 4 & 8 in Oman using TIMSS 2019 Standards - Al-Hudaify, Salim Said S; Nik Abdullah, Nik Md. Saiful Azizi (University College of Yayasan Pahang Press, 2024)
This study evaluated the Cambridge Mathematics series for grades 4 and 8 in Oman based on the Trends in International Mathematics and Science Study (TIMSS, 2019) standards. A sample of 140 pre-basic education mathematics teachers participated. Using a mixed-method approach (qualitative and quantitative), the researcher analyzed four Omani mathematics textbooks for grades 4 and 8 from the 2022/2023 academic year. Content analysis cards aligned with TIMSS (2019) standards, and the Context, Input, Process, Product (CIPP) Evaluation model was used as a tool. The analysis revealed that TIMSS standards were covered as follows: for grade 4, numbers (50%), geometric shapes and measurements (30%), and data (20%); for grade 8, numbers (30%), algebra (30%), geometry (20%), and data and probability (20%). Cognitive dimensions included knowledge (grade 4: 40%, grade 8: 35%), application (40% for both grades), and reasoning (grade 4: 20%, grade 8: 25%). Teachers and supervisors agreed that the Cambridge curriculum aligns well with the TIMSS cognitive standards.